Targeted Forward Genetics: Population-Scale Analyses of Allele Replacements Spanning Thousands of Base Pairs in Fission Yeast. Issue 12 (1st December 2019) - Storey, Aaron J; Wang, Hsin-Ping; Protacio, Reine U; Davidson, Mari K; Wahls, Wayne P
Abstract: Precise allele replacement (genome editing), without unwanted changes to the genome, provides a powerful tool to define the functions of DNA elements and encoded factors in their normal biological context. While CRISPR is now used extensively for gene targeting, its utility for precise allele replacement at population scale is limited because: (A) there is a strict requirement for a correctly positioned PAM motif to introduce recombinogenic dsDNA breaks (DSBs); (B) efficient replacements only occur very close to the DSBs; and (C) indels and off-target changes are frequently generated. Here we show, using a saturated mutation library with about 15, 000 alleles of the ade6 gene of Schizosaccharomyces pombe, that pop-in, pop-out allele replacement circumvents these problems. Two rounds of selection ensure that clones arise by homologous recombination with the target locus. Moreover, the exceptionally high efficiency allows one to carry out the process in bulk, then screen individual clones for phenotypes and genotypes. Alleles were introduced successfully throughout the region targeted, up to 1, 956 base pairs from the DSB. About 11% of mutant alleles were hypomorphic, demonstrating utility for analyses of essential genes and genetic elements. This process of "targeted forward genetics" can be used to analyze comprehensively, across thousands of base pairs within a specific target region, a variety of allelic changes, such as scanning amino acid substitutions, deletions, and epitope tags. The overall approach and optimized workflow are extensible to other organisms that support gene targeting.